KEPENTINGAN INDONESIA BELUM MERATIFIKASI KONVENSI 1951 DAN PROTOKOL 1967 MENGENAI PENGUNGSI INTERNASIONAL DAN PENCARI SUAKA - Afriandi, Fadli; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research discusses about the Indonesia’s Interest Unratified Yet The Convention 1951 and Protocol 1967 about International Refugees and asylum seekers. Indonesia is a strategic place to visit by international refugees and asylum seekers with the geographic condition of Indonesia. Indonesian is not partner from Convention 1951 and Protocol 1967. So Indonesian doesn’t have in handling international refugees and asylum seekers. But Indonesian’s gets active role in this case handling. For example, the case handling of refugee from Vietnam and Timor Leste. Indonesian experiences obstacle in haldling of this case like case like deciding refugee status that is still decided by UNHCR. If Indonesian ratifies it, so there are some usefuls like refugee problem resolving and more comprehensive asylum seekers. Until now Indonesian still faces by international refugees and asylum seekers. The author analyzes this case by finding data and facts through some literatures. The literature were collected from books, journals, media and website. Theory that is used in analyzing ungratified yet Convention 1951 and Protocol 1967 about Refugees International and asylum seekers is the theory of foreign policy with the rational actor models by Graham T. Allison. From this research can be seen as for the Indonesia’s Interest ungratified yet Convention 1951 and Protocol 1967 about International Refugees and asylum seekers is Indonesia has not been able to handle properly internally displaced persons. Other supporting factors such as the ability of the state, the phenomenon of refugees and asylum seekers to the effects of economic, social and security.Keywords: convention, protocol, internally displaced persons, refugee, asylum seeker